Compact MIMO Microstrip Antennas for USB Dongle Operating in 2.5–2.7 GHz Frequency Band. (27th September 2012) - Ssorin, Vladimir; Artemenko, Alexey; Maltsev, Alexander; Sevastyanov, Alexey; Maslennikov, Roman
Abstract : This paper considers design of microstrip MIMO antennas for an LTE/WiMAX USB dongle operating in the 2.5–2.7 GHz frequency band. The MIMO system includes two antenna elements with an additional requirement of high isolation between them that is especially difficult to realize due to size limitations of a USB dongle. Three approaches to achieve the needed system characteristics using microstrip PCB antennas are proposed. For the first design, high port-to-port isolation is achieved by using a decoupling techniques based on a direct connection of the antenna elements. For the second approach, high port-to-port isolation of the MIMO antenna system is realized by a lumped decorrelation capacitance between antenna elements feeding points. The third proposed antenna system does not use any special techniques, and high port-to-port isolation is achieved by using only the properties of a developed printed inverted-F antenna element. The designed MIMO antenna systems have the return loss S11 and the insertion loss S21 bandwidths of more than 200 MHz at the −8 dB level with the correlation coefficient lower than 0.1 and exhibit pattern diversity when different antenna elements are excited. Experimental measurements of the fabricated antenna systems proved the characteristics obtained from electromagnetic simulation.